2011
DOI: 10.7205/milmed-d-11-00069
|View full text |Cite
|
Sign up to set email alerts
|

Load-Carriage Distance Run and Push-Ups Tests: No Body Mass Bias and Occupationally Relevant

Abstract: Recent research has demonstrated body mass (M) bias in military physical fitness tests favoring lighter, not just leaner, service members. Mathematical modeling predicts that a distance run carrying a backpack of 30 lbs would eliminate M-bias. The purpose of this study was to empirically test this prediction for the U.S. Army push-ups and 2-mile run tests. Two tests were performed for both events for each of 56 university Reserve Officer Training Corps male cadets: with (loaded) and without backpack (unloaded)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Low content validity was rated in 14 commonly used physical performance tests. These results are in accordance with earlier findings suggesting that general physical fitness has shown to be a poor predictor of job performance [ 5 , 9 , 13 , 14 , 35 ]. For example, push-ups and sit-ups which are the most frequently occurring military tests in many countries, including Sweden [ 6 ] and the United States [ 5 , 36 ], were not considered to be content valid in the present work.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Low content validity was rated in 14 commonly used physical performance tests. These results are in accordance with earlier findings suggesting that general physical fitness has shown to be a poor predictor of job performance [ 5 , 9 , 13 , 14 , 35 ]. For example, push-ups and sit-ups which are the most frequently occurring military tests in many countries, including Sweden [ 6 ] and the United States [ 5 , 36 ], were not considered to be content valid in the present work.…”
Section: Discussionsupporting
confidence: 93%
“…To ensure valid evaluation of muscle strength and endurance according to the job requirements, occupational relevance is crucial [ 9 13 ]. Commonly used test batteries for soldiers have, however, in recent years, been challenged due to its lack of relevance [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vanderburgh and Crowder (11) used these data, along with data from tests on civilian subjects, to calculate the predicted performance of smaller and larger individuals on the standard fitness tests used by the Army, Air Force, and Navy. Vanderburgh went on, in 2011, to test whether the use of a 13.6-kg backpack would create equal performances across body weights, as discussed in the paragraph above (13). Another study looking at body mass effects in simulated military tasks using civilian men demonstrated a performance advantage for heavier subjects in 1 test (6).…”
Section: Discussionmentioning
confidence: 99%
“…If a pull-up test were to be devised that eliminated any body mass effect (greater relative strength of smaller individuals, greater absolute strength of larger individuals), the weight used would apparently need to be substantially greater than 11.4 kg. In a study using male Reserve Officers' Training Corps cadets, Vanderburgh et al (13) found that an added mass of 13.6 kg eliminated the body mass advantage of smaller individuals performing push-ups and doing a 3.2-km run. It is likely, therefore, that the pull-up test requires a greater added mass than the push-up and run tests to offset body mass bias.…”
Section: Discussionmentioning
confidence: 99%
“…For example, soldiers in an infantry battalion are exposed to completely different tasks and missions than fighter pilots, whereas the work day of a sailor is yet something else. An important part of this is the call for physical fitness tests that are contextually relevant on an occupational level, as it has been indicated that the relation between performance on some types of general physical fitness tests, and performance on common soldier tasks may be poor (Mitchell, White, & Ritschel, 2014;Spiering et al, 2012;Vanderburgh, Mickley, Anloague, & Lucius, 2011). In addition, it should be noticed that for a number of positions in the armed forces the physical performance demands are very limited.…”
Section: The Physiological Capacity Rationalementioning
confidence: 99%